Laying Low. - Thorkildsen, Asmund; Vold, Stale (Oslo : Kunstnernes Hus, 1997)
Andre, Carl ; Benglis, Lynda ; Bochner, Mel ; Le Va, Barry ; Morris, Robert ; Serra, Richard ; Smithson, Robert ; Wilke, Hannah ; Gonzalez-Torres, Felix ; Killey, Mike ; McGill, Melissa ; Miller, John ; Pardo, Jorge
biografie
Engels
boek